Formulation of Melatonin as a Cream and Studying the Release, Diffusion, and Stability of the Cream - Mohammed Mahmood Mohammed; Salim Abas Hamadi; Ashwaq Nejmelden Aljaf (College of Pharmacy / Mustansiriyah University, 2009)
The topical preparations are used to give localized effects at the site of their application by penetration of the drug into the underlying layers of the skin, mucous membranes, the cornea of the eye, nasal, rectal, vaginal or urethral mucosa. While some topical preparations are designed for the systemic absorption of drug substances in therapeutic quantities, like the transdermal drug delivery system. Melatonin is a hormone with multiple functions in human, synthesized and secreted by the pineal gland in response to changes in the darkness and light environment of the human. It is a powerful antioxidant and the most potent free radical scavenger known. Formulation of melatonin as a cream and studying the release and diffusion of the drug from this formula. Also evaluation the effect of temperature & storage time on the stability of melatonin in the prepared cream. Preparation of the cream base using the general method employed for the preparation of the various ointments, cream and gel bases, the fusion method. Then determination the in vitro release and diffusion of melatonin from the cream, also determination the stability of melatonin in the cream formula including the expiration date, Physical Properties, and pH of the cream. The release was increased with time, and after 6 hours, the amount of melatonin released was approximately 16.4% of the original amount of the drug, the. After 6 hours, the amount of melatonin diffused through mouse skin was 4.1% of the original amount of the drug. Arrhenius plot was utilized to predict the degradation rate constant and then the expiration date was 1.997 years. No change in the color and odor of the cream which stored at 50oC, 60oC and 70oC in a well-closed container and protected from light. Cream pH of the final product was 8.4 and after the storage period (45 days), the pH was around 8.2. The overall results of this study suggested that the prepared melatonin cream exerts its effects locally more than in a systemic way, which may increases its effectiveness in treatment of different skin pathological conditions locally, in the future work. In the future; it is possible to use different bases and chose the suitable one according to the study results, also enhancers, preservatives, and co-solvents could be used.